Chitosan nanoparticles as a sustainable alternative nutrient formulation in hydroponically grown Brassica rapa subsp. chinensis (L.) Hanelt microgreen and its adult vegetable. Issue 12 (15th October 2023) - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Wayayok, Aimrun; Nik Ibrahim, Nik nor Liyana; Hashim, Norhayati
ABSTRACT: Microgreens have been chosen as a sustainable dietary staple food due to their high nutritional value and short harvesting time. However, researches about the actual comparison of the nutritional value between microgreens and their respective adult vegetables is still missing. Furthermore, in a hydroponic system, chitosan nanoparticles (CNPs) can be used as an alternative sustainable nutrient formulation to the conventional/basic nutrient formulation solution. As a result, in this study, the quality, yield and nutritional content of hydroponically cultured microgreens versus adult of Bok Choy ( Brassica rapa subsp. Chinensi s (L.) Hanelt) vegetables were examined and evaluated in response to CNPs treatments and/or fertilizer supplementation that were grown under the same conditions and environments. CNPs have shown incredible potential as a sustainable alternative nutrient supplement in the growth of Bok Choy microgreens and adults. The nutritional value results backed up these claims as well. The addition of CNPs to conventional fertilizer has significantly increased the nutritional value of Bok Choy (microgreens and adults), supporting the claims of CNPs' ability to improve nutrient absorption and uptake. This is towards high-throughput green farming with better quality and yield using the nanotechnology platform.